Application of General Unified Threshold Models of Survival Models for Regulatory Aquatic Pesticide Risk Assessment Illustrated with an Example for the Insecticide Chlorpyrifos. (24th September 2020) - Brock, Theo; Arena, Maria; Cedergreen, Nina; Charles, Sandrine; Duquesne, Sabine; Ippolito, Alessio; Klein, Michael; Reed, Melissa; Teodorovic, Ivana; van den Brink, Paul J; Focks, Andreas
ABSTRACT: Mathematical models within the General Unified Threshold models of Survival (GUTS) framework translate time‐variable chemical exposure information into expected survival of animals. The GUTS models are species and compound specific and explicitly describe the internal exposure dynamics in an organism (toxicokinetics) and the related damage and effect dynamics (toxicodynamics), thereby connecting the external exposure concentration dynamics with the simulated mortality or immobility over time. In a recent scientific opinion on toxicokinetic–toxicodynamic (TKTD) models published by the European Food Safety Authority (EFSA), the GUTS modeling framework was considered ready for use in the aquatic risk assessment for pesticides and aquatic fauna. The GUTS models are suggested for use in risk assessment, if they are sufficiently validated for a specific substance–species combination. This paper aims to illustrate how they can be used in the regulatory environmental risk assessment for pesticides for a specific type of refinement, that is, when risks are triggered by lower tiers in acute as well as in chronic risk assessment and mortality or immobility is the critical endpoint. This approach involves the evaluation of time‐variable exposure regimes in a so‐called "Tier‐2C" assessment. The insecticide chlorpyrifos was selected as an example compound because a large data set was available. The GUTS models for 13 different freshwater arthropods and 8 different theoretical aquatic exposure profiles were used to calculate a series of GUTS‐based risk estimates, including exposure profile‐specific multiplication factors leading to 50% mortality or immobility at the end of the tested profile (LP50/EP50) as "margins of safety." To put the use of GUTS models within the tiered aquatic risk assessment into perspective, GUTS models for the 13 aquatic arthropods were also used to predict the environmental risks of a measured chlorpyrifos exposure profile from an experimental ditch study (Tier‐3 approach), and the results are discussed in the context of calibration of the tiered approach. Integr Environ Assess Manag 2021;17:243–258. © 2020 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: This paper illustrates how General Unified Threshold models of Survival (GUTS) models can be used in the regulatory environmental risk assessment for pesticides for the evaluation of time‐variable exposure regimes in a so‐called Tier‐2C assessment. For chlorpyrifos as an example compound, GUTS models for 13 different freshwater arthropods and 8 different theoretical aquatic exposure profiles were used to calculate a series of GUTS‐based risk estimates, including exposure profile‐specific "margins of safety" (LP50/EP50) values. GUTS models were put in perspective within the tiered aquatic risk assessment by comparing the predicted environmental risks of a measured chlorpyrifos exposure profile for 13 aquatic arthropods to results from an experimental ditch study. For the example data set (chlorpyrifos) the results of the Tier‐2C assessment using GUTS models were not in conflict with the principle of the tiered approach in that lower tiers should be more conservative than higher tiers.